(untitled) (Research, Society and Development, 2020)
Objectives: to verify the adequacy of the intake of iron and folic acid by pregnant women according to the recommendations recommended for this phase. Methods: Cross-sectional study involving 24 pregnant women attended at Basic Health Units. The pregnant women answered the questionnaire with socioeconomic and gestational data according to data present in the pregnant woman’s handbook from the Ministry of Health. The nutritional status of the pregnant women was classified according to the Body Mass Index gestational. The quantification of dietary intake regarding energy, macronutrients, iron and folic acid were calculated with the aid of the NutWin program. For purposes of adequacy, the results were compared with the reference values recommended by the World Health Organization for energy and marcronutrients and with that proposed by the Institute of Medicine for micronutrients during pregnancy. Results: Regarding nutritional status, 41.7% were eutrophic, 25% were overweight and 16.7% were obese. There was a statistically significant difference between ingestion and recommendation of carbohydrates (p <0.05), dietary folic acid (p <0.05), total folic acid (p <0.05), dietary iron (p <0, 05) and total iron (p <0.05). Of the 24 pregnant women, 58.3% were married, 83.3% completed high school or higher education and 100% had monthly income less than 5 minimum wages. Conclusion: Pregnant women present inadequacy when consuming micronutrients, which highlights the importance of individualized supplementation, based on the previous analysis of food intake of micronutrients and biomarkers, to better meet the individual needs of this period.